Evaluating Single Sign on Security Failure in Cloud Services - Cusack, B; Zadeh, E (Security Research Institute, Edith Cowan University, 2015)
The business use of cloud computing services is motivated by the ease of use and the potential financial cost reductions. Service failure may occur when the service provider does not protect information or when the use of the services becomes overly complex and difficult. The benefits also bring optimisation challenges for the information owners who must assess the service security risk and the degree to which new human behaviours are required. In this research we look at the risk of identity theft when ease of service access is provided through a Single Sign On (SSO) authorisation and ask: What are the optimal behavioural expectations for a Cloud service information owner? Federated identity management is a well-developed design literature for solutions to optimising human behaviours in relation to the new technologies. We briefly review the literature and then propose a working solution that optimises the trade-off between disclosure risk, human user risk and service security. Both breech and non-use of a system are failures.